Economic stabilisation and performance in West Africa: The role of fiscal and monetary policy - Ekundayo P. Mesagan; Ismaila A. Yusuf (African Governance and Development Institute (AGDI), 2019)
The study examines the impact of fiscal and monetary policy on economic performance and stabilisation in Nigeria, Gambia, and Ghana between 1980 and 2017. In the study, the real gross domestic product and the exchange rate are used to proxy economic performance and economic stabilisation respectively while fiscal policy is captured with deficit finance and government expenditure. Also, the broad money supply and monetary policy rate are used as proxies of monetary policy. The study obtains country-specific results using the fully modified ordinary least squares technique and findings show that monetary policy has insignificant effect on economic performance in Nigeria and the Gambia, but has significant impact in Ghana while fiscal policy significantly enhances economic performance in Nigeria and Gambia, but is insignificant in Ghana. Result also confirms that monetary policy significantly drives economic stabilisation in Nigeria and the Gambia, but insignificantly in Ghana while fiscal policy has insignificant impact on economic stabilisation in Ghana and Gambia, but significant in Nigeria. Thus, we conclude that fiscal policy is relatively more important in stimulating economic performance in Nigeria and Gambia while monetary policy is relatively more important in determining economic performance in Ghana. For economic stabilisation, both fiscal and monetary policies are important in Nigeria, both are ineffective in Ghana, while monetary policy is more important in the Gambia. The study recommends further reductions in monetary policy rate to put less pressure on the exchange rate and stabilise the various economies.
Keywords: E52; E62; E63; H62; F31; F43; 330; Fiscal Policy; Monetary Policy; Deficit Finance; Economic Performance